FRI0499 Long Term Survival of Immunosuppressive Therapies in Uveitis Patients. (15th July 2016) - Gόmez-Gόmez, A.; Rosales-Rosado, Z.; Arietti-Lόpez, L.; Arriola-Villalobos, P.; Lopez-Abad, C.; Pato-Cour, E.; Rodriguez-Rodriguez, L.
Abstract : Background: Uveitis encompasses a diverse group of inflammatory diseases associated with a significant risk of substantial and sometimes permanent visual loss. Although corticosteroids are the initial treatment, immunosuppressive therapy (IST) may be needed in case of inadequate response and/or side-effects. Most of the data regarding efficacy, tolerability and discontinuation rates of ISD in uveitis patients comes from clinical trials, as data from observational studies in uveitis are scarce. However, it is important to take into account that the trial settings are different from day-to-day clinical practice, which limits the validity of the extrapolated data to patients in daily practice. Objectives: To assess the long-term survival of ISTs in uveitis patients in real-life clinical practice. Factors associated with discontinuation were also analyzed. Methods: An observational retrospective longitudinal study of uveitis patients taking ISTs from 1989 to 2014 was conducted. The primary endpoint was IST discontinuation due to: clinical improvement, inefficacy, adverse drug reaction (ADRs), and other causes. Incidence rates of discontinuation (IR) per 100 patient-years were estimated. Variables associated with specific causes of discontinuation were analyzed using Cox bivariate and multivariate models. Results: We included 225 courses of IST in 95 patients (565.3 patient-years of observation). Cyclosporine [62 patients (65.3%)], methotrexate [44 (46.3%)], azathioprine [28 (29.5%)], and anti-TNFs [30 (31.6%)] were the most frequently used. Treatment was suspended in 116 cases (IR 20.5 with 95% confidence interval [17.1 to 24.6]). In the first year of therapy 75% continued on IST, and after ten years, the retention rate was 16%. The IRs due to clinical improvement, inefficacy and ADRs were 8.0 [5.9 to 10.7], 5.1 [3.6 to 7.4], and 4.4 [3.0 to 6.5], respectively. The IRs of all cause discontinuation for cyclosporine, methotrexate, azathioprine, and anti-TNFs were 21.7 [16.3 to 28.8], 10.9 [7.3 to 16.3], 18.7 [12.4 to 28.2], and 24.1 [16.0 to 36.2] per 100 patients-year, respectively. In the multivariate analysis, combined therapy was associated with a higher rate of discontinuation, regardless the cause. Presence of vasculitis was associated with a higher rate of discontinuation due to clinical improvement, and presence of macular edema was associated with higher risk of discontinuation due to inefficacy. Conclusions: The major causes of IST discontinuation in cohorts of uveitis patients were clinical improvement and inefficacy. Methotrexate showed the lowest rate of discontinuation, while anti-TNFs showed the highest rate. Combine therapy with IST was associated with higher discontinuation rate regardless the cause. Presence of vasculitis and macular edema were associated with a higher risk of discontinuation due to clinical improvement and inefficacy, respectively. Disclosure of Interest: None declared